A Review of Issues Concerning the Support for Fathers During Pregnancy: Research Trends in Japan (International Journal of Studies in Nursing, 2021)
Objective: To identify future issues in the development and implementation of support programs for fathers with the aim of preventing child abuse, we reviewed the domestic literature to determine the characteristics of support for fathers during pregnancy and identify research trends. Methods: The domestic literature was searched on January 31, 2021, using the Central Journal of Medicine ver.